Impact of Technological Innovations on CO2 Emissions: Evidence from Pakistan - Liaquat, Hira; Rana, Arslan Tariq; Farooq, Muhammad (Journal of Applied Research and Multidisciplinary Studies, 2023)
In Pakistan, production pattern is increasingly reliant on energy consumption, driven by economic and population growth. The country’s industries primarily employ non-renewable technologies which escalate emissions. Nevertheless, there is a growing emphasis on energy efficiency within the production sector, prompting efforts to stimulate technological innovation aimed at producing more efficient technologies for pollution mitigation. The current study investigated the impact of technological innovation on CO2 emissions within the context of Pakistan. Patents, both residential and non-residential, serve as proxies for technological innovations. Time series data covering the period from 1990-2019 was utilized and the study employed Johansen Cointegration, FMOLS (Fully Modified OLS), and VECM (Vector Error Correction Model) Granger Causality tests. The results from the Johansen Cointegration test indicated the presence of cointegration between CO2 emissions and technological innovation. FMOLS results revealed that non-residential patents have a significant mitigating effect on CO2 emissions in the long run, while energy consumption and Foreign Direct Investment (FDI) increase CO2 emissions in the long run. Interestingly, Gross Domestic Product (GDP) per capita showed no significant effect on mitigating pollution emissions. The VECM Granger Causality results indicate a long-term association between CO2 emissions, patents, GDP per capita, FDI, and energy consumption. These findings suggest that technological innovation plays a crucial role in reducing CO2 emissions. Consequently, it is recommended that the government increases investments in Research and Development (R&D) to promote cleaner technologies and control pollution emissions. Additionally, policymakers and government should work towards attracting environmentally friendly FDI to country’s industries.